Relevansi Undang Undang Perlindungan Konsumen dalam E-Commerce dengan Prinsip Hifz Al-Mal di Indonesia - Ramadhan, Ardiansyah Bagus; Adrebi, Fawwaz Sobirin (LoroNG: Media Pengkajian Sosial Budaya, 2025)
This study examines the relevance of the following legislation: No. 8 of 1999 on Consumer Protection (UUPK) with the principle of hifz.al-mal in maqashid syariah, as a means of achieving holistic consumer protection, especially in the era of e-commerce. The research focuses on the challenges of consumer protection in the digital digital and the potential for synergy between positive law and Islamic values. The objective of the study is to analyse the substance of the rights and obligations of consumers in the UUPK. The research aims to analyse the substance of the rights and obligations of consumers in the UUPK. explaining the principle of hifz al-mal as a moral and legal foundation Islam, and identifying the intersection of the two. The research uses a juridical method normatif dan menganalisis secara kualitatif dan komparatif sumber primer dan secondary sources, this study found a significant correlation between the rights and obligations consumers in UUPK (Articles 4 and 5) with the principle of hifz al-mal.Imam Asy-Syathibi's view of hifz al-mal as a fundamental (dharuriyat) provides a strong ethical foundation. Results: penelitian ini menunjukkan bahwa prinsip hifz al-mal sejalan dengan UUPK Pasal 4 dan 5, yang menekankan kehalalan harta (melarang riba, gharar, , and ikhtikar), distributive justice, and environmental protection. as collective property. It was concluded that the integration of hifz al-mal could strengthen the UUPK and create a more comprehensive, ethical and sustainable system for protecting consumers. comprehensive, ethical, and sustainable system, while also harmonising positive law with syariah Islam for the greater good.